The Influence of Training and Discipline on Employee Performance is Governed by Work Competence at the Job Training Center and Productivity Jambi Province - Bastian Bastian; Saiyid Syekh; M. Zahari (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the influence of Training and Discipline on Employee Performance mediated by Work Competencies at the Job Training and Productivity Center (BLKP) of Jambi Province. This study uses a descriptive and verifiable approach, focusing on 60 BLKP employees as the object of research. The analysis was carried out using the Partial Least Squares (PLS) method. From the results of the questionnaire, it was obtained that the training was considered effective with a total score of 2624. Employee discipline at BLKP Jambi is also relatively high, with a score of 1754. Employee Work Competencies showed a high score with a score of 2213, and Employee Performance was also included in the high category with a score of 2622. The results of the study show that Education and Training have a positive and significant effect on Work Competence, and Discipline also has a positive and significant influence on Work Competence. In addition, Training and Discipline each have a positive and significant effect on Employee Performance. Work Competencies also have a positive and significant influence on Employee Performance. Furthermore, the results of the analysis show that Work Competency significantly mediates the influence of Training and Discipline on Employee Performance in BLKP Jambi Province.